2010
DOI: 10.1080/00918369.2010.508314
|View full text |Cite
|
Sign up to set email alerts
|

Male Sexuality and Alfred Kinsey's 0–6 Scale: Toward “A Sound Understanding of the Realities of Sex”

Abstract: Using a 0-6 scale, Alfred Kinsey demonstrated that the complexity of human sexuality could best be represented on a continuum rather than as a binary. Kinsey developed the scale from models created by his predecessors in human sex research. A primary intention of the scale was to eradicate sexual identity categories altogether in order to eliminate sexual identity-based persecutions and to promote equal rights. As proponents and opponents of homosexual rights both depended on constructions of sexual identity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…(lesbian, genderqueer -trans * ) Sexuality researchers have long noted that sexual orientation and sexual orientation identity do not neatly map onto one another (Morgan, 2013;Sell, 1997;Worthington & Reynolds, 2009). In fact, a benefit of sexual orientation measurement is the ability to disaggregate such measurement from the stigma associated with sexual orientation identity labels (Drucker, 2010(Drucker, , 2012. Our participants' responses are consistent with this notion in that sociocultural attitudes and sexual prejudice were often the reasons behind the putative discrepancies between the scores on the scales and their sexual orientation identity.…”
Section: Social Identitymentioning
confidence: 99%
“…(lesbian, genderqueer -trans * ) Sexuality researchers have long noted that sexual orientation and sexual orientation identity do not neatly map onto one another (Morgan, 2013;Sell, 1997;Worthington & Reynolds, 2009). In fact, a benefit of sexual orientation measurement is the ability to disaggregate such measurement from the stigma associated with sexual orientation identity labels (Drucker, 2010(Drucker, , 2012. Our participants' responses are consistent with this notion in that sociocultural attitudes and sexual prejudice were often the reasons behind the putative discrepancies between the scores on the scales and their sexual orientation identity.…”
Section: Social Identitymentioning
confidence: 99%
“…However, sexual orientation is best considered multidimensional and a combination of attraction, identity, interests, and behavior (Feinstein & Galupo, 2020;Galupo et al, 2014;Noel & Lutz, 2020;Wolff et al, 2017) as well as sexual passion, urges, interests, fantasies, preferences, and affectional, social, and emotional preferences (Sell, 1997). Sexual orientation has also been conceptualized as being on a continuum (see Diamond, 2008;Drucker, 2010;Kinsey et al, 1948Kinsey et al, , 1953 for more background on this). For example, someone's sexual orientation could be bisexual if they are attracted to more than one sex/gender/gender identity, have intimate relationships/sexual relationships with people from more than one sex/gender/gender identity, and identify as bisexual.…”
Section: Using Sexual Orientation When We Mean Sexual Identitymentioning
confidence: 99%
“…Sexual orientation, however, is still largely viewed as a categorical phenomenon. It has been 75 years since Alfred Kinsey and his colleagues first published their groundbreaking book on sexual behavior (Kinsey et al, 1948), yet their insights into the continuous and somewhat dynamic nature of sexual orientation (SO) are still not widely accepted (Drucker, 2010). Based on interviews with more than 6,000 people, Kinsey and colleagues concluded that "It is a fundamental of taxonomy that nature rarely deals with discrete categories….…”
Section: Introductionmentioning
confidence: 99%